Analisis Perhitungan Pajak Penghasilan Badan Pada Perusahaan Jasa Konstruksi - Manuputty, Jeanne Laura Elizabeth; Sudradjat, Sudradjat (Jurnal Ilmiah Akuntansi Kesatuan, 2018)
This research was conducted at PT. Anugerah Abba Prakarsa at Jalan Pangeran Jayakarta 45 No. A5 Jakarta Barat DKI Jakarta. The purpose of this study is to know compliance calculation of corporate income tax on construction services at PT. Anugerah Abba Prakarsa with Peratura Pemerintah no. 51 year 2008 Jo Peraturan Pemerintah no. 40 year 2009 and know how reporting mechanism of annual income tax return of construction service company at PT. Anugerah Abba Prakarsa. This research is a qualitative research with descriptive approach. Research that produces descriptive data in the form of written or oral words of people and behavior that can be observed. In other words, this research is called qualitative research because it is a study that does not hold calculations. The analytical method used is comparative descriptive writing that compares the similarities and differences between two or more facts and properties of the object under study based on a particular frame of mind. The results showed that the analysis and calculation of income tax of PT. Anugerah Abba Prakarsa has been in accordance with Peraturan Pemerintah no. 51 year 2008 JO Peraturan Pemerintah no. 40 years 2009. However, there are some time PT. Abba Prakrsa's prize suffered a constraint which resulted in the increase of the Corporate Income Tax rate to 4% from the Tax Basis. Keywords : PSAK 16, fixed assets, financial statement